THE MEANING USED IN KATTY PERRY SONG “DARK HORSE” - Adeliya Putri Renjani; Emeliya S. D. Damanik; Filzah Nazhifah; Depimaya S. Harahap; Putri F. Manik (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Abstract This study aims to analyze the various meanings contained in the song Dark Horse by Katty Perry. This research uses descriptive qualitative analysis method to conduct research. The research sample is a song entitled Dark Horse by Katty Perry with 12 stanzas of lyrics. The results of the study show that there are two dominant meanings in this song, namely denotative meaning and connotative meaning. The denotative meaning is the meaning according to the dictionary, while the connotative meaning is the implied meaning that interprets the overall context in the song. The general message contained in this song is to talk about love, don't hesitate in expressing love so you won't regret it later, but never betray love if you don't want that person to turn into a vicious “dark horse” that ravages your life.